ENT300 Dolce Amore / Nur Syafiqa Suhandi... [et.al] - Suhandi, Nur Syafiqa; Abdillah, Nur Aidili Fadzillah; Jamaldin, Nur Amalina Azyan; Jaafar, Dewi Farima (2015)
Our business name is Dolce Amore. Our business has been decided to be in the form of partnership, which consists of 5 members. Each partner that involve in this business had agreed to contribute RM 10,000.00 each to this business. We agreed that Nur Syafiqa Binti Suhandi as our General Manager, Nur Aidili Fadzillah Binti Abdillah as the Marketing manager, Nur Amalina Azyan Binti Jamaldin as the Operational Manager, Nurul Hasikin Binti Jamri as Administration Manager and Dewi Farima Binti Jaafar as the Financial Manager. The selection of Manager is based on their experience, skills and ability. Our main business activity, is selling and produce ice cream. The Dolce Amore is located at G3940, ground floor, ST3 Shopping Mall, Jalan Simpang Tiga, Kuching. We choose this location because it is situated in the center area of people passage from every place in Kuching and it is surrounded by residential areas, universities and colleges, schools, private and government offices, banks, shops lot and most important it is also located just opposite of the most visited and most busiest mall from day to night in Kuching which is The Spring Mall.